2021
DOI: 10.1159/000515865
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lenvatinib-Transcatheter Arterial Chemoembolization Sequential Therapy for Patients with Intermediate-Stage Hepatocellular Carcinoma

Abstract: <b><i>Introduction:</i></b> We evaluated the efficacy and safety of lenvatinib-transcatheter arterial chemoembolization (LEN-TACE) sequential therapy for patients (<i>n</i> = 88) with intermediate-stage hepatocellular carcinoma (HCC). <b><i>Methods:</i></b> Eighty-eight patients who obtained tumor control by LEN treatment were analyzed; 30 received LEN followed by TACE (LEN-TACE sequential therapy), and 58 received LEN monotherapy. Propensity score ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 35 publications
(45 reference statements)
1
68
0
Order By: Relevance
“…This might be the cause of the result. In addition, compared with other studies in the literature, the PFS of lenvatinib-TACE was 5.5 -11.6 months ( 30 32 ), while the PFS of our LePD1-TACE triple treatment achieved 10.4 months, our results were in the upper range. Notably, the different results between these studies and our data should be viewed with caution.…”
Section: Discussionsupporting
confidence: 49%
“…This might be the cause of the result. In addition, compared with other studies in the literature, the PFS of lenvatinib-TACE was 5.5 -11.6 months ( 30 32 ), while the PFS of our LePD1-TACE triple treatment achieved 10.4 months, our results were in the upper range. Notably, the different results between these studies and our data should be viewed with caution.…”
Section: Discussionsupporting
confidence: 49%
“…The subgroup analysis presented here indicates that the Child–Pugh score is a critical factor for the prognosis of intermediate-stage HCC. Ando et al and Hiraoka et al also reported that the Child–Pugh score was critical for disease prognosis [ 27 , 28 ]. The high proportion (36%) of patients with a Child–Pugh score of 6, versus ~ 22% in REFLECT [ 29 ] and ~ 28% in IMbrave150 [ 30 ], may have led to the shorter median OS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated lenvatinib-TACE sequential therapy versus lenvatinib alone in patients with intermediate-stage HCC who were not unsuitable for TACE. The results showed that the OS of the combined treatment group was significantly longer than that of the lenvatinib group (not reached vs. 16.9 months, p = 0.007) ( 105 ). Two studies suggest that early lenvatinib-TACE sequential therapy may be a good combination therapy for patients with intermediate-stage HCC who are not suitable for TACE.…”
Section: What Else Can We Do?mentioning
confidence: 99%